Turnover Kinetics of Pancreatic Macrophages in Lean and Obese Diabetic Mice - Ma, Ziyuan; Ruedl, Christiane (Frontiers in Endocrinology, 2022)
Pancreatic resident macrophages, a heterogeneous family of cells with distinct origins and phenotypes, are the main myeloid cells in exocrine and endocrine tissues. Adult exocrine F4/80hi macrophages consist of three different subsets based on the embryonic marker Tim-4 and MHC II expression. Their frequencies shift during aging and obesity with the Tim-4-MHCII+ fraction becoming the predominant subpopulation in the inter acinar stroma. Endocrine resident F4/80hi macrophages are more homogenous and represent the prevalent leukocyte fraction residing within the islets in both lean and obese mice. We used an adult fate mapping mouse model to characterize turnover kinetics within the pancreatic resident macrophages under normal homeostasis and obese diabetic conditions. We demonstrate that islet resident macrophages show unique replenishment kinetics, with embryonic macrophages being gradually replaced by bone marrow-derived monocytes with increasing age. Their replenishment was independent of the CCL2/CCR2 axis. Furthermore, we confirmed that both exocrine Tim-4+MHCIIlow and Tim-4+MHCII+ fractions are long-lived and primarily independent from bone marrow-derived monocytes, whereas exocrine Tim-4-MHCII+ macrophages are gradually replaced through a CCR2-dependent influx of bone marrow-derived monocytes in aging. Moreover, we show that obesity and type 2 diabetes does not affect the turnover kinetics of any macrophage subpopulation residing in the pancreas. Our study uncovers new insights on pancreatic macrophage biology in aging and obesity.